Pengaruh Corporate Social Responsibility terhadap Nilai Perusahaan dengan Green Accounting sebagai Variabel Moderasi (Studi Empiris pada Perusahaan yang Terdaftar dalam Indeks SRI-KEHATI di Bursa Efek Indonesia Periode 2018–2021) - Widianti, Widianti (Jurnal KIAFE, 2025)
This study examines the effect of Corporate Social Responsibility disclosure on firm value, with green accounting as a moderating variable, in companies listed in the SRI-KEHATI Index on the Indonesia Stock Exchange during the 2018–2021 period. The study employs a quantitative causal approach using secondary data obtained from annual reports and sustainability reports. The sample was selected through purposive sampling and consisted of 14 companies, resulting in 56 firm-year observations. Corporate Social Responsibility was measured using the Corporate Social Responsibility Disclosure Index based on the GRI-G4 guidelines, firm value was measured using Price-to-Book Value, and green accounting was proxied by PROPER ratings issued by the Ministry of Environment and Forestry. Data were analyzed using simple linear regression and Moderated Regression Analysis with SPSS. The results show that Corporate Social Responsibility has a negative and significant effect on firm value. Green accounting is unable to moderate the relationship between Corporate Social Responsibility and firm value. The coefficient of determination is 9.7% for the direct-effect model and 10.2% for the moderated model, indicating limited explanatory power.